Autoantibody response and pregnancy-related pathology induced by combined LPS and tetanus toxoid hyperimmunization in BALB/c and C57BL/6 mice. (March 2015) - Petrušić, Vladimir; Todorović, Nevena; Živković, Irena; Dimitrijević, Rajna; Muhandes, Lina; Rajnpreht, Irena; Dimitrijević, Ljiljana
Abstract Recent data concerning antiphospholipid syndrome (APS) induction have shown that β2-glycoprotein I (β2GPI) binds lipopolysaccharide (LPS), which results in conformational changes, exposition of a cryptic epitope and possible pathological anti-β2GPI antibody production. In order to investigate the effects of LPS on the induction of APS-related pathology, we performed hyperimmunization of BALB/c and C57BL/6 mice with LPS, alone or in combination with tetanus toxoid (TTd), a protein structurally similar to β2GPI. We report that, although high affinity pathological anti-β2GPI antibodies were produced in all groups of animals, the reproductive pathology was recorded only in mice that received both LPS and TTd, implying on the important roles of both infections and molecular mimicry in APS pathogenesis. Moreover, APS-related reproductive pathology was more pronounced in BALB/c (lowered fertility and fecundity) than C57BL/6 mice (lowered fecundity), which correlated well with the disruption in natural antibody network observed in BALB/c mouse strain.